2021
DOI: 10.3390/polym13060876
|View full text |Cite
|
Sign up to set email alerts
|

Incorporation of In Situ Synthesized Nano-Copper Modified Phenol-Formaldehyde Resin to Improve the Mechanical Properties of Chinese Fir: A Preliminary Study

Abstract: Phenol-formaldehyde (PF) resin, modified using nano-copper with varying contents (0 wt%, 1 wt%, 3 wt%), was manufactured to improve the mechanical properties of Chinese fir. The morphology, chemical, micromechanical and micromechanical properties of the samples were determined by transmission electron microscopy (TEM), atomic force microscopy (AFM), environmental scanning electron microscopy (ESEM), Fourier transform infrared spectroscopy (FTIR), nanoindentation (NI) and traditional mechanical testing. The TEM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…This has been reported for the hardness of the fiber cell walls impregnated with copper nanoparticles and modified resin. Researchers found that the copper nanoparticles diffused easily into the intercellular spaces and the cell wall and the formation of a complex cross-linking in the cell wall [41]. This contrasts with water-borne solutions that use metal oxides, which undergo a hydrolytic reaction when reacting with hemicelluloses; therefore, they end up oxidizing the cell wall components and consequently reduce the properties of wood [42].…”
Section: Hardnessmentioning
confidence: 99%
“…This has been reported for the hardness of the fiber cell walls impregnated with copper nanoparticles and modified resin. Researchers found that the copper nanoparticles diffused easily into the intercellular spaces and the cell wall and the formation of a complex cross-linking in the cell wall [41]. This contrasts with water-borne solutions that use metal oxides, which undergo a hydrolytic reaction when reacting with hemicelluloses; therefore, they end up oxidizing the cell wall components and consequently reduce the properties of wood [42].…”
Section: Hardnessmentioning
confidence: 99%
“…[10] Phenol formaldehyde (PF) resin, due to its excellent bonding strength, heat resistance, water resistance, and abrasion resistance, [11,12] currently is considered as one of the most commonly used adhesives in wood and bamboo bonding. [13][14][15] . However, due to the highly crosslinked degree of the PF resin network molecular structure after curing, brittle fracture is easy to occur.…”
mentioning
confidence: 99%